Designing Sustainable Technologies, Products and Policies 2018
DOI: 10.1007/978-3-319-66981-6_17
|View full text |Cite
|
Sign up to set email alerts
|

Agri-Food Waste Streams Utilization for Development of More Sustainable Food Substitutes

Abstract: Substitution of food out of alternative biomass sources is aimed to supply consumers with food products similar in nutrition and with lower environmental impact compared to conventional products. At current state of development, meat substitutes are not competitive with chicken meat, except for plant based meat analogs (although they have weaker nutritional profile). Upscaling, further technological development and use of agri-food waste as main source substrate can assure the environmental benefits of insects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…As) should be observed (Mleczek et al 2016)Cultured meatCultured meat demands large amounts of energy, resulting in an environmental impact more than 4 times higher than chicken (Smetana et al 2015)The biochemical composition of meat might be altered to make it healthier, e.g. the content of poly-unsaturated fatty acids can be increased (Post 2012)Public acceptance depends on an efficient production and resemblance to meat (Post 2012)The quality of the substrates and other compounds used in the culture medium imposes more risks than microbial contamination (Bhat and Fayaz 2011)MicroalgaeSmetana et al (2018) have associated the production of meat alternatives from microalgae to high energy consumption and low water footprintThey present an interesting nutritional protein value as well as high amounts of omega-3 fatty acids (Weinrich and Elshiewy 2019)The taste of Spirulina has been described as not fitting a stand-alone item. The use of flavorings and seasonings needs further investigation (Grahl et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As) should be observed (Mleczek et al 2016)Cultured meatCultured meat demands large amounts of energy, resulting in an environmental impact more than 4 times higher than chicken (Smetana et al 2015)The biochemical composition of meat might be altered to make it healthier, e.g. the content of poly-unsaturated fatty acids can be increased (Post 2012)Public acceptance depends on an efficient production and resemblance to meat (Post 2012)The quality of the substrates and other compounds used in the culture medium imposes more risks than microbial contamination (Bhat and Fayaz 2011)MicroalgaeSmetana et al (2018) have associated the production of meat alternatives from microalgae to high energy consumption and low water footprintThey present an interesting nutritional protein value as well as high amounts of omega-3 fatty acids (Weinrich and Elshiewy 2019)The taste of Spirulina has been described as not fitting a stand-alone item. The use of flavorings and seasonings needs further investigation (Grahl et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In another work, Smetana et al (2018) have reported the energy, land and water used in the production of meat substitutes. Mycoprotein figures among the most efficient alternatives when considering land (< 2 m 2 a/kg; compared to 5–7 m 2 a for chicken and 7–8 m 2 a for pork) and water use (~ 500 L/kg).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of insect-based food (1 kg) could be decreased to 2 kWh of energy use, around 1 kg CO 2 eq. of GWP, 1.5 m 2 of land use and 0.1 m 3 of water use (Smetana et al 2018).…”
Section: From Waste Streams To Insects Feedmentioning
confidence: 99%
“…However to make mycoprotein based protein competitive to chicken, apart from further technological innovation, utilization of agri-food wastes has been recommended. These wastes, as substrates, have been reported to reduce the consumption of energy to 10 kW h, environmental impact to 2-4 kg CO 2 -eq, and land use to 0.5 m 2 [46]. More importantly, the mycoprotein footprint is mainly from energy consumption, which can be reduced through decarbonization.…”
Section: Environmental Impactmentioning
confidence: 99%